Modelling the environmental impact of omni-channel purchasing in the apparel industry: the role of logistics. Issue 4 (4th November 2019) - Giuffrida, Maria; Mangiaracina, Riccardo; Miragliotta, Giovanni; Perotti, Sara; Tumino, Angela
This paper addresses an identified need of quantitative models in the rising field of omni-channel (OC) purchasing sustainability. It contributes with a detailed assessment of the environmental impact of two processes, click and collect (C&C) and mobile shopping in store (MSiS), highlighting the weight of logistics activities. An activity-based model is developed and applied to a base case, that best represents the average purchasing process in the apparel industry, considering both the retailer's and the customer's perspectives. Sensitivity analyses are performed as well. Results show that MSiS is less sustainable than C&C, mainly due to the heavier impact of transport. For both configurations, the most critical parameter is the distance between the customer house and the store, whereas the customer profile and the location of the customer house (urban vs. extra-urban area) are additional significant factors for MSiS. The results of this study are also compared to previous research in the field of e-commerce environmental sustainability.